1996
DOI: 10.1097/00006842-199603000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Posttraumatic Stress Disorder

Abstract: This article analyzes the literature on the treatment of posttraumatic stress disorder (PTSD). It briefly exposes the theoretical basis for each treatment modality and extensively examines pharmacological, behavioral, cognitive, and psychodynamic therapies, as well as group and family therapies, hypnosis, inpatient treatment, and rehabilitation. Articles were identified by scanning Medline and PsychLit for all papers in English reporting treatment of PTSD. Anecdotal case reports were, then, excluded. Eighty on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
1
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(100 citation statements)
references
References 93 publications
1
93
1
5
Order By: Relevance
“…Even though research points towards a diverse emotional profile underlying PTSD development, the alleviation of fear remains the main focus of therapeutic interventions (e.g. Shalev, Bonne, & Eth, 1996). Advancement in the understanding of emotional factors that underlie PTSD emphasizes possible benefits of more idiosyncratic treatment approaches that aim to change guilt-related feelings and cognitions associated with the traumatic event.…”
Section: Discussionmentioning
confidence: 99%
“…Even though research points towards a diverse emotional profile underlying PTSD development, the alleviation of fear remains the main focus of therapeutic interventions (e.g. Shalev, Bonne, & Eth, 1996). Advancement in the understanding of emotional factors that underlie PTSD emphasizes possible benefits of more idiosyncratic treatment approaches that aim to change guilt-related feelings and cognitions associated with the traumatic event.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the magnitude of symptom improvement from baseline levels of PTSD severity was not suggestive of full remissions in the current study group, although a substantial within-group effect size was observed in the primary PTSD outcome measure. Partial rather than full remission of PTSD symptoms has been observed in a prior study 42 of both pharmacotherapy and psychotherapy in patients with PTSD.…”
Section: Discussionmentioning
confidence: 81%
“…De plus, il semble y avoir consensus général chez les cliniciens et les chercheurs à l'effet que les modalités de traitement individuel ne sont pas vraiment utiles pour aborder l'éven-tail complet des problèmes cliniques, tels que les difficultés interpersonnelles fréquemment observées chez les individus traumatisés Shalev et al, 1996).…”
Section: Psychothérapie Pour Le Tspt Aperçuunclassified